An IOT-Based Automated Patients Health Monitoring System - Sharma, Romsha (International Journal of Computer Sciences and Engineering, 2019)
— Healthcare is given the extreme importance now a- days by each country with the advent of the novel corona virus. So, in this aspect, an IoT based health monitoring system is the best solution for such an epidemic. Internet of Things (IoT) is the new revolution of internet which is the growing research area especially in the health care. With the increase in use of wearable sensors and the smart phones, these remote health care monitoring has evolved in such a pace. IoT monitoring of health helps in preventing the spread of disease as well as to get a proper diagnosis of the state of health, even if the doctor is at far distance. In this paper, a portable physiological checking framework is displayed, which can constantly screen the patient’s heartbeat, temperature and other basic parameters of the room. We proposed a nonstop checking and control instrument to screen the patient condition and store the patient’s information in server utilizing Wi-Fi Module based remote correspondence.